2014
DOI: 10.1111/cea.12370
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the novel SHIP1 activator AQX‐1125 on allergen‐induced responses in mild‐to‐moderate asthma

Abstract: SummaryBackground SH2-containing inositol-5 0 -phosphatase 1 (SHIP1) is an endogenous inhibitor of the phosphoinositide-3-kinase pathway that is involved in the activation and chemotaxis of inflammatory cells. AQX-1125 is a first-in-class, oral SHIP1 activator with a novel anti-inflammatory mode of action. Objective To evaluate the effects of AQX-1125 on airway responses to allergen challenge in mild-to-moderate asthmatic patients. Methods A randomized, double-blind, placebo-controlled, two-way crossover study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…Recent clinical studies with SHIP-1 agonists found a moderate therapeutic effect in patients with allergic asthma. 24 Although our results would suggest that activation of SHIP-1 in T cells and DCs would enhance disease severity, it is possible that SHIP-1 agonists have a net positive therapeutic effect through actions on specific leukocyte subsets, such as mast cells and basophils, where it has been shown to be an important regulator of their activation. [25][26][27][28] Placing these observations in the context of the current work, it is likely that specific targeting of SHIP-1 activity, either positively or negatively, in a lineage-specific manner could lead to improved control of AAI.…”
Section: Discussionmentioning
confidence: 66%
“…Recent clinical studies with SHIP-1 agonists found a moderate therapeutic effect in patients with allergic asthma. 24 Although our results would suggest that activation of SHIP-1 in T cells and DCs would enhance disease severity, it is possible that SHIP-1 agonists have a net positive therapeutic effect through actions on specific leukocyte subsets, such as mast cells and basophils, where it has been shown to be an important regulator of their activation. [25][26][27][28] Placing these observations in the context of the current work, it is likely that specific targeting of SHIP-1 activity, either positively or negatively, in a lineage-specific manner could lead to improved control of AAI.…”
Section: Discussionmentioning
confidence: 66%
“…SHIP is more amenable to activation and a small molecule activator of SHIP-1, AQX-1125, and is effective in reducing p-Akt and reducing mediator release, mast cell activation, and leukocyte chemotaxis in vitro (Stenton et al, 2013b) and inflammation in allergeninduced and cigarette smoke-induced pulmonary inflammation in mice in vivo (Stenton et al, 2013a). A recent clinical trial of oral AQX-1125 in patients with mild asthma showed a significant reduction in later response after allergen challenge and a (nonsignificant) reduction in inflammatory biomarkers (Leaker et al, 2014). The drug is well tolerated, suggesting that it might be a potential treatment of asthma and COPD.…”
Section: B Inhibiting Phosphoinositide-3-kinase-aktmammalian Target mentioning
confidence: 97%
“…Since metformin is relatively well tolerated with chronic use it might be a suitable therapy for treating multimorbidity. PI3K signalling may also be inhibited by activators of the endogenous inhibitor SHIP-1 [138] and such drugs have already entered clinical trials for treatment of allergic disease [139]. Low concentrations of theophylline have been shown to inhibit oxidant-activated PI3Kδ, which may be involved in reduced SIRT1 levels after oxidative stress [29].…”
Section: Pharmacological Therapiesmentioning
confidence: 99%